2016
DOI: 10.1177/1557988316647942
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Intention to Obtain Colorectal Cancer Screening Among African American Men in a State Fair Setting

Abstract: Racial disparities in health among African American men in the United States are appalling. African American men have the highest mortality and incidence rates from colorectal cancer compared to all other ethnic, racial, and gender groups. Juxtaposed to their white counterparts, African American men have colorectal cancer incidence and mortality rates 27% and 52% higher, respectively. Colorectal cancer is a treatable and preventable condition when detected early, yet the intricate factors influencing African A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 36 publications
3
17
0
Order By: Relevance
“…Several factors were associated with intention-age, education, perceived threat, attitude, perceived norm, and perceived behavioral control. These results are consistent with findings of factors associated with screening from the literature, (McEachan et al 2011;Rogers et al 2016), including the positive association of intention with perceived threat. Studies over the past decade have demonstrated that African Americans who perceive a low threat of having a child with sickle cell disease are less likely to get screened (Gallo et al 2010;Gustafson et al 2007).…”
Section: Discussionsupporting
confidence: 91%
“…Several factors were associated with intention-age, education, perceived threat, attitude, perceived norm, and perceived behavioral control. These results are consistent with findings of factors associated with screening from the literature, (McEachan et al 2011;Rogers et al 2016), including the positive association of intention with perceived threat. Studies over the past decade have demonstrated that African Americans who perceive a low threat of having a child with sickle cell disease are less likely to get screened (Gallo et al 2010;Gustafson et al 2007).…”
Section: Discussionsupporting
confidence: 91%
“…However, results from the educational series suggested that adding spiritual themes did not result in significant behavioral changes among attendees. This might further validate the role of other contributing factors, such as lack of health insurance, lack of access to early-detection screening, medical system mistrust, and socioeconomic disadvantages as mediators influencing early detection screening behavior changes among African-American men, and thus, should be considered alongside the other well-documented barriers to CRC screening [ 101 , 102 ].…”
Section: Discussionmentioning
confidence: 99%
“…In clinical settings, strategies to better utilize patient navigation systems to emphasize the importance of screening and enhance educational outreach for healthcare providers who provide routine care for African-American men could conceivably aid in lowering the cost of promoting CRC screening, particularly among low-income patients [ 105 ]. In community settings, interventions that could efficaciously dispel the mistrust and ease the anxiety associated with screening are vital to promoting screening among African-American men [ 19 , 102 ]. According to Adams and colleagues in a recent systematic review, African-American men often face unique challenges and express substantial fears about medical procedures associated with CRC [ 106 108 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alarmingly, they also reported several emotional barriers to seeking early medical help, including being worried about what the doctor might find or for wasting the doctor's time, feeling too scared or embarrassed to seek help and not feeling confident when talking about their symptoms (Al-Azri et al, 2019). Attitudes toward CRC screening are a reliable predictor of help-seeking behaviors (Rogers et al, 2018). Such attitudes are influenced by several factors including age, perceived barriers, subjective norms, socioeconomic status, educational level and previous knowledge of CRC screening (McCaffery et al, 2003;Rogers et al, 2018).…”
Section: Attitudes Toward and Knowledge Of Colorectal Cancer Screeninmentioning
confidence: 99%
“…Attitudes toward CRC screening are a reliable predictor of help-seeking behaviors (Rogers et al, 2018). Such attitudes are influenced by several factors including age, perceived barriers, subjective norms, socioeconomic status, educational level and previous knowledge of CRC screening (McCaffery et al, 2003;Rogers et al, 2018).…”
Section: Attitudes Toward and Knowledge Of Colorectal Cancer Screeninmentioning
confidence: 99%